An Analysis of Code-Mixing And Code-Switching Used By Maudy Ayunda In Perspektif Metro TV - Mac Aditiawarman; Husnul Hayati (Fakultas Sastra Universitas Ekasakti, 2021)
This research focused on the analysis of the types of code-mixing and code-switching between Maudy Ayunda and Robert in the interview in Perspektif Metro TV on Monday 30th December 2019. The researcher applied sociolinguistic theory, especially the theories on types and reasons of code-mixing and code-switching proposed by Hoffman (1991) and how many codes in their utterances based on Myers-Scotton theory (2006). This research applied the descriptive qualitative method. After analyzing the data, there are 71 cases of code-mixing and 68 cases of code-switching. For the types of code-mixing, there is 63 intra-sentential, 15 intra-lexical and 3 involving a change in pronunciation. For types of code-switching, there is 64 inter-sentential, and 4 are established with the previous speaker. For the reasons of code-mixing/code-switching, the researcher found 31 data of talking about a particular topic, 1 data of quoting somebody else, 2 being emphatic about something, 6 of repetition used for classification and 1 of clarifying the speech content for the interlocutor. For the matrix in code-mixing, Indonesian 82% as matrix language and English 18% as an embedded language, and in code-switching, Indonesian 54% as matrix language and English 46%as an embedded language.